Forms of Spending Free Time by Generation Z of Consumers in Poland and Determinants of Their Choice - Jolanta TARAPATA (Communications of International Proceedings, 2020)
The paper presents the specificity of the group of consumers belonging to the so-called generation Z. Regardless of whether the biological or educational criterion of age is taken into account, this segment of the market requires detailed knowledge, as well as the determination of specific features that distinguish it from the adult part of society. The aim of the paper is to extend knowledge about the forms of spending free time by young consumers and the determinant of their choice. The study uses secondary sources of information, which made it possible to characterise free time, as well as aspects related to its quantity, deficit, and management by young consumers. Thematic books were used, as well as studies on the characteristics of the contemporary generation Z. To illustrate the considerations undertaken, reference was made to own research aimed at seeking a link between young consumers' preferred free time activities and their family environment, i.e. the material conditions of the family and the associated pocket money of young consumers, as well as their individual predispositions, i.e. their system of values and life goals, their interests and constraints, i.e. their time deficit. It has been assumed that these groups of factors have a decisive influence on the choice of activities undertaken by young consumers in their free time.
Keywords: Consumer Behavior; Free Time Spending; Generation Z.